Risk factors for mortality among patients undergoing major amputations due to infected diabetic feet - Cardoso, Natália Anício (J Vasc Bras, 2018)
BACKGROUND: Foot ulcers in patients with diabetes are a major public health problem and are often associated with lower limbs amputation and mortality in this population. OBJECTIVES: To investigate the risk factors associated with mortality in patients with infected diabetic foot ulcers and major lower limb amputations. METHODS: This was an observational, retrospective, case-control study with a sample of 78 patients with infected diabetic foot ulcers who had major lower limb amputations at a Vascular Surgery Service at a university hospital. RESULTS: The mean age of the study sample was 63.8 ± 10.5 years, 54 (69.2%) were male, mean serum creatinine was 2.49 ± 2.4 mg/dL and mean serum hemoglobin was 7.36 ± 1.7 g/dL. There was a 47.4% rate of readmissions to the same hospital. Transtibial amputation was performed in 59.0%; and transfemoral amputation in 39.7% of the sample. In this sample, 87.2% had a positive culture, predominantly (68.0%) monomicrobial and nosocomial infection of ulcers was observed in 30.8%. The most common bacterial genera were Acinetobacter spp. (24.4%), Morganella spp. (24.4%) and Proteus spp. (23.1%). No bacterial genus was identified as a predictor of death. Creatinine level ≥ 1.3 mg/dL (OR 17.8; IC 2.1-150) and transfemoral amputation (OR 4.5; IC: 1.3-15.7) were associated with death. CONCLUSIONS: Serum creatinine levels ≥ 1.3 mg/dL and transfemoral amputation were risk factors for death.